Computer Analysis Of A simplified Eye Model - Nabi, T.A. Abdul; Mohammed, K.A.; Mohammed, H. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Computer analysis of simple eye model is performed in the present work by using the Zemax optical design software 2000E . The most important optical parameters of the eye were calculated such as the effective focal length (EFL) , the image spot size at the retina and found to be in a reasonable agreement with the values needed for the laser retinal treatment .The present eye model leads to an effective wavelength and we found the image spot diagram at the surface of the retina and the wavefront error which are provided at zero field angle. This gives a good evidence of the validity of the model in one hand, and can be used to determine the compatibility of any optical design intended for visual applications. By using the pulse frequency doubled Nd:YAG laser 532 nm can be used for the  to treatment the retina.